Pathophysiology of Endometriosis: Role of High Mobility Group Box-1 and Toll-Like Receptor 4 Developing Inflammation in Endometrium - Yun, Bo Hyon (PLoS One, 2016)
Oxidative stress has been proposed as a potential factor associated with the establishment and progression of endometriosis. Although a few studies have shown possible mechanisms which may play roles in development, progression of endometriosis, few are known in regards of initiation of the disease, especially in the relationship with endometrium. The aim of our study was to investigate whether normal endometrium may be changed by Damage-associated molecular patterns (DAMPs), which may contribute developing pathologic endometrium to induce endometriosis. Endometrial tissues were obtained from 10 patients with fibroids undergoing hysterectomy at a university hospital. High mobility group box-1 (HMGB-1), which is a representative DAMP, has been chosen that may induce alteration in endometrium. In preceding immunohistochemistry experiments using paraffin-block sections from endometriosis (N = 33) and control (N = 27) group, retrospectively, HMGB-1 expression was shown in both epithelial and stromal cell. HMGB-1 expression was significantly increased in secretory phase of endometriosis group, comparing to the controls. To examine the alteration of endometrial stromal cell (HESC) by oxidative stress in terms of HMGB-1, cell proliferation and expression of its receptor, TLR4 was measured according to recombinant HMGB-1 use. Cell proliferation was assessed by CCK-8 assay; real-time PCR and western blotting were used to quantify Toll like receptor 4 (TLR4) mRNA and protein expression respectively. A TLR4 antagonist (LPS-RS) and an inhibitor of the NF-κB pathway (TPCA-1, an IKK-2 inhibitor) were used to confirm the relationships between HMGB-1, TLR4, and the NF-κB pathway. Passive release of HMGB-1 was significantly proportional to the increase in cell death (P<0.05). HESCs showed significant proliferation following treatment with rHMGB-1 (P<0.05), and increased TLR4 expression was observed following rHMGB-1 treatment (P<0.05) in a concentration-dependent manner. Treatment with a TLR4 antagonist and an NF-κB inhibitor resulted in suppression of rHMGB-1-induced HESC proliferation (P<0.05). Levels of IL-6 were significantly decreased following treatment with an NF-κB inhibitor (P<0.05). Our results support the development of altered, pathological endometrium resulted from oxidative stress in normal endometrium. These findings may provide important insights into the changes in endometrium linking the development and progression of endometriosis.